The novel immunoglobulin super family receptor SLAMF9 identified in TAM of murine and human melanoma influences pro-inflammatory cytokine secretion and migration - Dollt, Claudia; Michel, Julia; Kloss, Loreen; Melchers, Susanne; Schledzewski, Kai; Becker, Kathrin; Sauer, Andrea; Krewer, Andreas; Koll, Franziska; Schmieder, Astrid (Cell death & disease, 2018)
Melanoma is a highly immunogenic tumor with a good response to treatment with immune checkpoint inhibitors. Tumor-associated macrophages (TAMs) play an important immunosuppressive role in such tumors and have therefore been identified as possible future therapeutic targets in oncology. The aim of this study was to identify novel immunoregulatory receptors specifically expressed on TAM. Expression of Slamf9, a member of the signaling lymphocytic-activating molecule (Slam) immunoreceptor family, was found to be upregulated in a gene expression analysis of murine bone marrow-derived macrophages (BMDM) stimulated with tumor-conditioned medium of B16F1 melanoma cells. SLAMF9+ macrophages were identified in human and murine melanomas by using self-generated antibodies against human and murine SLAMF9. A comprehensive immunohistochemical analysis of tissue microarrays detected SLAMF9+ TAM in 73.3% of human melanomas, but also in 95.5% of naevi of melanoma patients and in 50% of naevi from healthy controls. In addition, 20% of melanomas and 2.3% of naevi from melanoma patients displayed a positive SLAMF9 expression also in melanocytic cells. No SLAMF9 expression was detected in naevus cells of healthy donors. Although SLAMF9 has no intracellular signaling motif, a comprehensive functional analysis revealed that the molecule was able to significantly enhance TNF-α secretion after LPS-stimulation. In addition, SLAMF9 delayed the wound closure of RAW 264.7 cells in a scratch assay, while proliferation and cell death were not affected. Taken together, SLAMF9 is a novel type-I-transmembrane receptor with immunomodulatory properties in macrophages. Further studies are required to evaluate whether SLAMF9 classifies as a promising future therapeutic target in melanoma.
Gesehen am 03.04.2020